The Influence of Knowledge Management and Self-Efficacy on Employee Performance at PT Cipta Nirmala (Semen Gresik Hospital) - Tasya Nabila Pramana; Endang Iryanti (Indonesian Journal of Business Analytics, 2023)
Human resources are the main asset in a business entity so it is very necessary to manage and develop professionalism to be able to produce superior and maximum performance. This study aims to determine the effect of knowledge management and self efficacy on employee performance at PT Cipta Nirmala (Semen Gresik Hospital). The population taken in the study were employees at PT Cipta Nirmala (Semen Gresik Hospital) in the non-health section, totaling 112 employees. The sampling technique in this study used probability sampling and used the slovin technique so that the sample used amounted to 53 respondents. This research uses quantitative methods. This research analysis method uses Partial Least Square (PLS). The conclusion in the results of this study shows that knowledge management has a significant positive effect on the performance of employees of PT Cipta Nirmala (Semen Gresik Hospital) and self efficacy has a significant positive effect on the performance of employees of PT Cipta Nirmala (Semen Gresik Hospital).